Pacific finance sector brief federated states of Micronesia. (Pacific finance sector briefs., 2019)
The country finance sector comprises the Bank of the Federated States of Micronesia and foreign owned Bank of Guam. The Banking Board regulates the banking system. There are also small credit unions, which are not currently subject to government oversight. The Federated States of Micronesia is moderately monetized and the public sector dominates the economy. Private enterprises have weak participation in the economy as they face difficult business conditions, including the slow progress with land reforms. As a result, there is a scarcity of bankable projects and limited private sector growth.